2016
DOI: 10.1136/jnnp-2016-313356
|View full text |Cite
|
Sign up to set email alerts
|

The association between delays in screening for and assessing dysphagia after acute stroke, and the risk of stroke-associated pneumonia

Abstract: . (2016). The association between delays in screening for and assessing dysphagia after acute stroke, and the risk of stroke-associated pneumonia. Journal of Neurology, Neurosurgery and Psychiatry. https://doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
149
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 21 publications
6
149
0
3
Order By: Relevance
“…As a further ray of hope, 2 recent prospective, large, multicenter studies with positive results were published: one found early dysphagia screening to be associated with reduced risk of stroke-related pneumonia and disability [9]. The other reported pneumonia incidence to increase 1% per day of delay in dysphagia screening and comprehensive assessment by an SLT [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a further ray of hope, 2 recent prospective, large, multicenter studies with positive results were published: one found early dysphagia screening to be associated with reduced risk of stroke-related pneumonia and disability [9]. The other reported pneumonia incidence to increase 1% per day of delay in dysphagia screening and comprehensive assessment by an SLT [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Early dysphagia screening and appropriate management including high-intensity treatment may reduce complications, lead to a more favorable outcome, and lower case fatality [7-11]. Current treatment guidelines for acute stroke care, for example, in Germany, take these study results into account and make respective recommendations [12].…”
Section: Introductionmentioning
confidence: 99%
“…Díaz-Navarro et al [1] found that the presence of dysphagia in patients with acute stroke on hospital admission is an independent predictor of short-term outcome from stroke. Early identification of dysphagia reduces the risk of aspiration, malnutrition, dehydration, aspiration pneumonia, and choking [2, 3]. There is some evidence to suggest that a dysphagia screening protocol is associated with lower rates of pneumonia [3, 4] and, when combined with an acute stroke team protocol, has potential to significantly decrease costs to health services by reducing length of hospital stay and antibiotic treatment [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Early identification of dysphagia reduces the risk of aspiration, malnutrition, dehydration, aspiration pneumonia, and choking [2, 3]. There is some evidence to suggest that a dysphagia screening protocol is associated with lower rates of pneumonia [3, 4] and, when combined with an acute stroke team protocol, has potential to significantly decrease costs to health services by reducing length of hospital stay and antibiotic treatment [4, 5]. However, although there is a predominant focus on swallow screening in stroke in the literature, screening for dysphagia is important in all high-risk populations such as dementia, head and neck cancer, pulmonary disease, Parkinson’s disease, and critical illness [6].…”
Section: Introductionmentioning
confidence: 99%
“…25 Early screening for and managing dysphagia reduces pneumonia rates. 26,27 Up to 15% of patients will have persistent dysphagia requiring artificial nutrition, 28 and a gastrostomy tube may be the only option for nutritional support in these patients. It is unclear whether this intervention will contribute to similar improvement in patient-centered outcomes with established stroke prevention therapies.…”
mentioning
confidence: 99%